Peepoo! Uncovering the Impact of the Eastern European Immigration Shock on Wages Employment and Unemployment in the UK - Sara Lemos (Institute of Labor Economics (IZA), 2025)
No empirical evidence has ever been reported that the large inflow of accession immigrants – following the 2004 expansion of the European Union – led to a fall in wages or employment, or a rise in unemployment in the UK between 2004 and 2006. This immigration shock was unexpectedly larger and faster – as well as more concentrated into areas and occupations – than anticipated, seemingly more akin to an exogenous supply shock than most immigration shocks. Exploiting rich but underused individual level data from the Lifetime Labour Market Database (LLMDB) we estimate the effect of this immigration shock on wages, employment and unemployment of natives and previously existing immigrants in the UK. We confirm once again the finding of little evidence that the inflow of accession immigrants led to a fall in wages, a fall in employment, or a rise in unemployment of natives in the UK between 2004 and 2006. However, we uncover, for the first time, novel evidence of adverse employment and unemployment effects for low paid existing immigrants as a result of the accession immigration inflow. This is more severe for low paid immigrants and young low paid immigrants as well as for long term unemployed immigrants.
Keywords: J22; 330; wages; employment; immigration; Central and Eastern Europe; UK